UNIDADE DE APRENDIZAGEM: O EDUCAR PELA PESQUISA NO COTIDIANO POR MEIO DO ESTUDO DA QUÍMICA - Lazzarotto, Veridiana (2017)
This current work aimed to study how the construction and application of scientific knowledge occurs in the discipline of Chemistry, concerning the inorganic functions with high school students of a public school. After developing a Learning Unit with this content, through the analysis of testimonies, interviews, classroom occurrences, experimental activities and written production, it was intended and understood how the construction and application of knowledge occurs in the processes of educating through research, contributing to the formation of more active subjects and capable of interacting positively in the environment in which they live. The work reports the origins of the research as well as the author's life as a student and educator, justifying the choice of the theme, the problem and the research questions that guide the work. For the development of the study, there are some theoretical possibilities that guide reflections about education through research, learning units, reflection on science and sustainability, the commitment to educate and the interpersonal relations between educator and students. The learning unit was built taking into account the previous ideas of the students, which were categorized and analyzed, allowing the structuring of activities. From the analysis, it was observed how the activities developed allowed the identification of changes in the initial knowledge of the subjects, highlighted by the complexity of their conceptions in the descriptions at the end of the study. The findings suggest that the pedagogical strategies developed in the research allowed for the expansion of knowledge, thus confirming the relevance of the approach of differentiated methodologies in the classroom for the realization in the teaching-learning process. The conclusions highlight the importance of approaching relevant themes associated with their daily lives, considering information about the students' previous knowledge and interests, the complexity and application of the knowledge acquired, as well as the educator-student interaction in the research development.